Techniko-takticeskoe masterstvo borcov i zreliscnost' sportivnych poedinkov - Martem'janov, Ju. G.; Gabov, M. V. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The Authors offer the model of the process of perfection of technical-tactical skill of wrestlers in the view of the necessity of change of rules of the competitions directed on the increase of spectacliness of the duels.